Experimental Study of CO2-saturated Water – Illite/Kaolinite/Montmorillonite System at 70-80 °C, 100-105 Bar. (July 2017) - Sendula, Eszter; Páles, Mariann; Szabó, Barbara Péter; Udvardi, Beatrix; Kovács, István; Kónya, Péter; Freiler, Ágnes; Besnyi, Anikó; Király, Csilla; Székely, Edit; Szabó, Csaba; Falus, György
Abstract: Low permeability caprock prevents migration of injected CO2 towards the surface and potable water reservoirs. As a result of geochemical reactions among caprock minerals and CO2 -saturated pore water, physical properties such as porosity, permeability and tortuosity may change, which could affect the sealing capability of caprocks. Due to the common high clay mineral content of caprocks, the reactivity of these minerals should be well-studied at CO2 -saturated reservoir conditions. The main aim of this study is to understand better the geochemical behavior of CO2 –brine–clay mineral system by using laboratory experiments at reservoir conditions on reference clays.